Application of theoretical and methodological components of nursing care - Rosa del Socorro Morales-Aguilar; Gloria Elena Lastre-Amell; Alba Cecilia Pardo-Vásquez (Universidad Francisco de Paula Santander, 2016)
Introduction: the theoretical and methodological components are the proper expertise in nursing, and it refers to models, theories, care process, taxonomy of nursing diagnoses, system of nursing intervention classification, and system of outcomes classification, which base nursing care into professional practice. Methodology: research was performed on Google Scholar, reviewing the databases of Scielo, Ciberindex, Index Enfermería, Dialnet, Redalyc, Medline, identifying 70 published articles between 2005-2015, and selecting 52 of them. The keywords used were: nurse care, nursing diagnostic, classification, nursing theory, in spanish and portuguese. Results: training students, receive knowledge in the nursing process, NANDA International, classification of the interventions, nurse results and theoretical components. The Dorothea Orem, Callista Roy, Nola Pender, Virginia Henderson, Florence Nightingale, and Betty Neuman theories are applied. The application of the nursing process is limited and low familiarity with the international taxonomy by nurse professionals in the assistance area is noticed. Conclusions: the challenge of nursing is to continue to solidify the scientific knowledge and to undo the gap between theory and practice.